Strategi Marketing Mix Karya Sanggar Batik Katura di Kota Cirebon - Ika Rusdika Dewi; Widiana Indah Permata; Adi Iryanto (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study aims to analyze the implementation of marketing mix strategies at the Katura Batik Studio in Cirebon City as an effort to increase competitiveness while preserving batik cultural heritage. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants include studio owners, artisans, and batik consumers. The analysis was conducted by referring to the 7P marketing mix concept, which includes product, price, place, promotion, people, process, and physical evidence. The results show that the marketing strategy implemented by the Katura Batik Studio is not only oriented towards economic aspects, but also on cultural values. The resulting products are of high quality with typical Cirebon motifs such as Mega Mendung, which have been maintained for generations. The pricing strategy is adjusted to the level of production complexity, while promotion is carried out through social media, word of mouth, and cultural events. In addition, the role of human resources, traditional production processes, and physical evidence such as showrooms also strengthen the consumer experience. The findings of this study indicate that optimal integration of marketing mix elements can increase consumer loyalty while strengthening the position of batik as a local cultural identity. This research contributes to the development of culture-based marketing strategies in the creative MSME sector.